FAKTOR PENDUKUNG DAN PENGHAMBAT PENGEMBANGAN WISATA DANAU LAET DI DESA SUBAH KABUPATEN SANGGAU - Munawar, Munawar; Buwono, Sri; Anasi, Putri Tipa (Universitas Tanjungpura, 2024)
This research is entitled Supporting and Inhibiting Factors for the Development of Lake Laet Tourism Objects in Subah Village, Tayan Hilir District, Sanggau Regency. Lake Laet is a rain-fed lake that has a large expanse of water and has small islands in the middle. This research aims to analyse the factors that support and hinder the development of Lake Laet tourist attraction, where Lake Laet has become a priority area for tourism development in accordance with Sanggau Regency Regional Regulation Number 7 of 2021. This research uses a qualitative method with descriptive analysis. The data source in this research is the facilities and infrastructure available at Lake Laet tourist attraction and the data are the results of field observations and the results of interviews with tourists, tourist attraction managers and the Sanggau Regency tourism office. Based on the results of the research, it is concluded that the factors that support the development of Lake Laet tourism include Attractiveness, Facilities, Accessibility and Government Support. The factors that hinder the development of Lake Laet tourism include lack of promotion, simple tourist attraction development programmes, poor entrance roads, lack of professional labour and limited internet networks. Based on the above conclusions, the suggestions given are the need for cooperation between the government in this case the Sanggau Regency tourism office and the private sector on an ongoing basis, evaluating existing development in order to carry out integrated and sustainable facility development